Improvement of urinary symptoms after bladder biopsy: A case of pathologically proven allergy‐related cystitis during administration of nivolumab. Issue 4 (23rd March 2021) - Yajima, Shugo; Nakanishi, Yasukazu; Matsumoto, Shunya; Tanabe, Kenji; Sugano, Masato; Masuda, Hitoshi
Abstract : Introduction: We present a case of cystitis, which was considered to be an immune‐related adverse event associated with nivolumab administration. Case presentation: A 47‐year‐old man suffered from sudden onset urinary symptoms after 18 cycles of nivolumab treatment for stage IV pulmonary adenocarcinoma. Urine culture and urine cytology were both negative. The symptoms were inferred to be related to nivolumab administration, and a bladder biopsy under spinal anesthesia was performed. The histopathological examination showed the evidence of allergic‐related cystitis. We planned to administer corticosteroids, but the urinary symptoms disappeared after the bladder biopsy. Nivolumab treatment was continued without recurrent bladder symptoms. Conclusion: We reported a case of cystitis after treatment with nivolumab, which served as a reminder to consider the possibility of immune‐related adverse events as a potential cause for any symptoms that develop during treatment with immuno‐oncology drugs.